Mechanochemical synthesis and thermoelectric properties of TiFe2Sn Heusler alloy. (June 2021) - Novitskii, Andrei; Serhiienko, Illia; Nepapushev, Andrei; Ivanova, Alexandra; Sviridova, Tatyana; Moskovskikh, Dmitry; Voronin, Andrei; Miki, Hiroyuki; Khovaylo, Vladimir
Abstract: Heusler alloys have attracted much attention due to their low toxicity, mechanical and thermal stability, relative abundance, and potential for thermoelectric power generation. Herein, we demonstrate that TiFe2 Sn full-Heusler alloy can be obtained by a mechanochemical synthesis of metal precursors followed by spark plasma sintering. It is shown that thus prepared samples exhibit the ordered structure (Heusler phase, MnCu2 Al-type). The influence of processing parameters on microstructure, phase composition, and thermoelectric properties of TiFe2 Sn is studied. The thermoelectric figure of merit of the sample fabricated under optimal mechanochemical processing parameters is comparable to that of TiFe2 Sn synthesized using the conventional route. Thus, our results indicate that the mechanochemical synthesis is a facile, scalable, and cost-effective route for the preparation of TiFe2 Sn Heusler alloys. Highlights: TiFe2 Sn prepared by mechanochemical synthesis followed by spark plasma sintering. Mechanochemical synthesis performed at room temperature. Figure of merit similar to that of TiFe2 Sn synthesized by a conventional path.